Perancangan Sistem Informasi Absensi Berbasis Android Menggunakan Geolocator - Hikmah Abdillah, Hilman; Najiyah, Ina (Jurnal Teknik Indonesia, 2023)
Introduction: The development of information and communication technology greatly influences the current civilization which makes it possible to simplify work in an organization. One of them is CV Raudha Design which has utilized information technology in various aspects of operations, but does not include employee attendance which is still manual using an attendance card. Purpose: to create an android-based attendance application system to get data in realtime and accompanied by coordinates using a geolocator when employees are absent. Method: The development of this application uses the waterfall method. Testing the system using black box testing. System coding uses the dart language with the flutter framework. Results: The results of this study are the design of an android-based attendance information system to make it easier for employees to take attendance online. Conclusion: It can be concluded that the attendance application uses an Android-based geolocator to facilitate the attendance process because there is no need to fill in and out of attendance data on the attendance paper.